Chronic exertional compartment syndrome: current management strategies - Buerba RA; Fretes NF; Devana SK; Beck JJ (Dove Medical Press, 2019)
Rafael A Buerba, Nickolas F Fretes, Sai K Devana, Jennifer J BeckDepartment of Orthopaedic Surgery, David Geffen School of Medicine at UCLA, Los Angeles, CA, USAAbstract: Chronic exertional compartment syndrome (CECS) is an underdiagnosed condition that causes lower and upper extremity pain in certain at-risk populations. Lower-extremity CECS is most often observed in running athletes and marching military members. Upper-extremity CECS is most commonly seen in rowers and professional motorcyclists. Although early outcome research on CECS has been based mostly on adult male patients, there has been an increase in the number of studies in pediatric and adolescent patient populations, particularly in females. Evaluation of CECS must include a thorough history and physical exam to rule out other causes of exertional leg pain, but differential diagnosis must remain high on the list. Needle manometry can be used to confirm diagnosis of CECS by measuring intracompartmental pressure. Operative treatment of CECS with fasciotomy has been shown to be effective in resolution of CECS, and new surgical techniques are being developed. In the pediatric population, endoscopy-assisted compartment release has provided high success rates with low complication rates. Nonoperative management of CECS is more commonly described in the literature, and consists of cessation of activities, altering foot-strike pattern, physical therapy, taping, and injections of botulinum toxin A. Nonetheless, larger samples and a more diverse population are needed to better understand the outcomes of nonoperative management. There have been fewer studies on upper-extremity CECS, given its rarity. Success has been found in the treatment of upper-extremity CECS with open fasciotomy, but more studies are needed to understand the efficacy of minimally invasive techniques in the upper extremity. Further research also needs to be done to understand why a large portion (approximately 20%) of the patient population does not experience full resolution of symptoms after fasciotomy.Keywords: chronic exertional compartment syndrome, CECS lower extremity, CECS upper extremity, pediatric CECS